COMPARATIVE STUDY OF GLYCOLIC ACID AND SALICYLIC ACID PEELS IN PATIENTS OF MELASMA - Dr. Swati Shandilya, Dr. Poonam Tapsale Dr. Swapna khatu, Dr Nitin Chaudhary (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The management of melasma is challenging and requires a long-term treatmentplan Besides HQ, other topical agents for which varying degrees of evidence for clinical efficacy exist include azelaic acid